STRATEGI PEMBELAJARAN GURU IPS DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA - Fitriani, Fitriani (Makassar Journal of Social Sciences, 2023)
This study aims to describe the learning strategy social studies teacher at SMP Negeri 2 Makassar to describe the discipline of students in Junior High School 2 Makassar to determine the relationship of learning strategies social studies teachers in improving student learning discipline SMP Negeri 2 Makassar.This study uses statistical analysis of quantitative research with a population of 360 students in Junior High School 2 Makassar, and the sample totaled 36 students at SMP Negeri 2 Makassar. Data collection was done by using observation, questionnaire, and documentation. The data analysis technique used is descriptive statistical analysis and statistical analysis infensial.The results showed that the description of the learning strategy social studies teacher at SMP Negeri 2 Makassar classified in the category of " good ", seen from the questionnaire in terms of ekspository and heuristics. While the description of learning discipline of students classified in the category of " good " , seen by the positive value of the questionnaire in terms of discipline and negative discipline. Social studies teacher learning strategy has no effect on student learning discipline but have a relationship. That is, the better the teacher learning strategy, the better the students' learning discipline and the results are normal and acceptable